2011
DOI: 10.1177/0017896911398234
|View full text |Cite
|
Sign up to set email alerts
|

The prostate exam

Abstract: Objective: To help students, residents, and general practitioners to improve the technique, skills, and reproducibility of their prostate examination. Methods: We developed a comprehensive guideline outlining prostate anatomy, indications, patient preparation, positioning, technique, findings, and limitations of this ancient art of urological evaluation. Results: The prostate exam was the first diagnostic test used for prostate cancer screening and other urological conditions. Although several alternative proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Thus for 4 fingertip impressions on the posterior surface of the prostate was inferred as 40 cc volume [18]. Romero et al, [3] documented a volume of 20 g for Grade I, 30 g for Grade I/II, 40 g for Grade II, 50 g for Grade II/III, 60 g for Grade III and 80 g or greater for Grade IV in their study. In their study Lodh, et al concluded that estimation of prostate size may be overestimated or underestimated by DRE but it gives a rough idea of prostate volume estimation [2].…”
Section: Original Research Articlementioning
confidence: 79%
See 2 more Smart Citations
“…Thus for 4 fingertip impressions on the posterior surface of the prostate was inferred as 40 cc volume [18]. Romero et al, [3] documented a volume of 20 g for Grade I, 30 g for Grade I/II, 40 g for Grade II, 50 g for Grade II/III, 60 g for Grade III and 80 g or greater for Grade IV in their study. In their study Lodh, et al concluded that estimation of prostate size may be overestimated or underestimated by DRE but it gives a rough idea of prostate volume estimation [2].…”
Section: Original Research Articlementioning
confidence: 79%
“…International Journal of Medical Research and Review Available online at: www.medresearch.in 67 | P a g e current study used DRE grading mentioned by Lodh et al which is a modification of DRE grading described by Romero et al due to its simplistic nature [2,3]. The size of prostate lobes on DRE is not a criterion as to the size of their protrusion into the bladder.…”
Section: Original Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Multinomial logistic regression was used to explore BPH- and ED-related factors associated with short- and long-term improvement beyond baseline and maintenance in urinary and sexual outcomes (in sub-scales with at least 10 men for stable estimation). Factors considered were individual measures of BPH (pre-surgical prostate size, IPSS score, and reported use of BPH medications, overall and separately by type), as well as a composite BPH outcome (prostate size ≥ 40 g [ 19 ], IPSS score ≥ 8 [ 20 ], or medication use), and measures of sexual dysfunction (pre- and post- surgical ED medication and device use). Sensitivity analyses were performed by: (1) adjusting for factors significantly associated with improvement or maintenance in at least one urinary or sexual outcome; (2) using the lower bounds of the EPIC-50 sub-scale-specific MCID ranges to classify participants; (3) excluding men with pre-surgical EPIC-50 scores too high to experience improvement (i.e., higher than the value obtained by subtracting the sub-scale specific MCID from 100); (4) restricting to men with complete data on specific urinary and sexual outcomes at baseline, 5 weeks and 12 months; and (5) repeating the analyses using the 6 month follow-up data.…”
Section: Methodsmentioning
confidence: 99%
“…Digital rectal examination showed clinical grade I prostate,2 irregular, non-nodular, with decreased anal tone. The patient was non-diabetic and non-hypertensive.…”
Section: Case Presentationmentioning
confidence: 99%